Ethoxy acetalated dextran nanoparticles for drug delivery: A comparative study of formulation methods - Mira Behnke; Paul Klemm; Philipp Dahlke; Blerina Shkodra; Baerbel Beringer-Siemers; Justyna Anna Czaplewska; Steffi Stumpf; Paul M. Jordan; Stephanie Schubert; Stephanie Hoeppener; Antje Vollrath; Oliver Werz; et al. (Elsevier, 2023)
Dextran-based polymers, such as ethoxy acetalated dextran (Ace-DEX), are increasingly becoming the focus of research as they offer great potential for the development of polymer-based nanoparticles as drug delivery vehicles. Their major advantages are the facile synthesis, straightforward particle preparation and the pH-dependent degradation of the particles that can be fine-tuned by the degree of acetalation of the polymer. In this study we have shown that Ace-DEX can not only compete against the commonly used and FDA-approved polymer poly(lactic-co-glycolic acid) (PLGA), but even has the potential to outperform it in its encapsulation properties, e.g., for the herein used anti-inflammatory leukotriene biosynthesis inhibitor BRP-187. We used three different methods (microfluidics, batch nanoprecipitation and emulsion solvent evaporation) for the preparation of BRP-187-loaded Ace-DEX nanoparticles to investigate the influence of the formulation technique on the physicochemical properties of the particles. Finally, we evaluated which production method offers the greatest potential for achieving the demands for a successful translation from research into pharmaceutical production by fulfilling the basic requirements, such as reaching a high loading capacity of the particles and excellent reproducibility while being simple and affordable.